System of relationship between institutional participants of investment process in the region - O. Goyher; A. Danilov (Вестник университета)
In this article the types of relationships between institutional participants of the investment process in the region are presented. The concept of "interaction field" is formulated and proved. Classification groups ties among the blocks of economic development institutions in the implementation of investment policy in the region are presented.